2005
DOI: 10.1095/biolreprod.104.038810
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Expression of the Novel Germ Cell Antigen TEX101 During Mouse Gonad Development

Abstract: Prospermatogonia, or gonocytes, are the cells that differentiate from primordial germ cells to the first mature type of spermatogonia in the developing testis. Although prospermatogonia play a central role in this stage (i.e., prespermatogenesis), the details regarding their characterization have not been fully elucidated. Recently, we identified a novel mouse testicular germ cell-specific antigen, TES101 reactive protein (TES101RP), in the adult mouse testis. The protein TES101RP is also designated as protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 31 publications
3
65
0
2
Order By: Relevance
“…For quantitative data, see also Table II. the most promising candidates. TEX101 is a very specific marker for both male and female germ cells during gonadal development (28). TEX101 is a membrane glycoprotein expressed on the cell surface of germ cells during spermatogenesis but shed to the seminal plasma at the late stages of post-testicular sperm maturation (29).…”
Section: Discussionmentioning
confidence: 99%
“…For quantitative data, see also Table II. the most promising candidates. TEX101 is a very specific marker for both male and female germ cells during gonadal development (28). TEX101 is a membrane glycoprotein expressed on the cell surface of germ cells during spermatogenesis but shed to the seminal plasma at the late stages of post-testicular sperm maturation (29).…”
Section: Discussionmentioning
confidence: 99%
“…By the screening, we identified many meiosisor germ cell-specific genes, including Stra8, 26 Rec8, 27 Tex12 28 and Tex101. 29,30 Of the isolated genes, we focused on a gene encoding a protein that had a PR domain, a derivative of SET domain which has been known to act as catalytic domain for histone lysine methylation. 31 PR-domains bear 20-30% sequence identity with SET domain, and have catalytic activity for histone methylation similar to SET domain-containing proteins.…”
Section: Meisetz a Meiosis-induced Histone Methyltransferase Specifimentioning
confidence: 99%
“…In contrast, during spermatogenesis, TEX101 first appears on the plasma membranes of prospermatogonia within the immature seminiferous cords of the fetal testis [6]. Although it is not expressed on spermatogonia, TEX101 reappears on meiotic cells including spermatocytes, spermatids, and testicular sperm following puberty [6]. Finally, TEX101 is shed from the cell surface of epididymal sperm during transport through the caput epididymis [7].…”
mentioning
confidence: 99%
“…TEX101, a highly N-glycosylated glycosylphosphatidylinositol (GPI)-anchored glycoprotein [5], was originally identified as a protein containing the antigen epitope for a specific mAb, called TES101, produced by immunizing female mice with an allogenic testicular homogenate [4]. Previous studies by our research group have demonstrated that TEX101 is a unique germ cell marker that is expressed during gametogenesis [4][5][6][7][8][9] and shows sexually dimorphic expression in developing gonadal tissues. In the ovary, oogonia temporarily express TEX101 during the fetal period [6], but the molecule is not detected in the sexually mature ovary [4].…”
mentioning
confidence: 99%